ANALYSIS OF PRODUCT QUALITY AGAINST DECISION OF PURCHASING KERUPUK HALAL IN CIAMIS DISTRICT - Fitrnaty Adirestuty; Ika Dartika; Tsania Salsabila (Syari'ah Economics, 2021)
Halal "kerupuk" are one of the snacks that are in demand by all people. In order to maintain the stability of cracker sales, the company strives to maintain the quality of halal kerupuk. In fact, currently found many cracker products whose quality is considered poor by consumers. This study aims to determine the effect of product quality on increasing the sales volume of halal kerupuk in Cijeungjing District, Ciamis Regency. This type of research is quantitative research using correlational research methods, which is a method used to determine the magnitude of the relationship between variables. Data collection techniques using questionnaires, documentation studies, and observations. Data analysis used simple regression analysis. The results of data analysis showed that there was an effect of product quality on sales of halal fertilizers in Cijeungjing District, Ciamis Regency.